Hubungan Kepuasan Kerja dengan Kinerja Petugas Rekam Medis di RSUP Dr. Sardjito Yogyakarta - Desy Rachmawati; Sustin Farlinda; Sugeng Sugeng; Gamasiano Alfiansyah (Politeknik Negeri Jember, 2021)
Job satisfaction is an important factor that can affect employee performance. If the employee feel satisfiedwith their work, the employee will produce good performance, and vice versa. Based on observations andinterviews with one of the medical recorders, it is known that they never get a reward if they work well inaccordance with applicable procedures. In addition, facilities that support their work such as dumbwaiter andtroli sometimes suffer damage. This condition resulted in work performed by medical recorders at RSUP Dr.Sardjito Yogyakarta is not optimal, so it will affect job satisfaction. The impact of this condition was found alateness providing the patient's medical record to the health services unit or sometimes wrong distribution ofmedical record files that are not in accordance with the patient's destination services unit. This conditioncauses the examination of patients by health professional also hampered. The purpose of this research is toidentify the relationship of job satisfaction with medical recorder at RSUP Dr. Sardjito Yogyakarta. The methodof data collection in this research is a questionnaire. Analysis of the data used is univariate analysis andbivariate analysis using the Spearman rank correlation test. The results showed that the level of jobsatisfaction of medical recorders at RSUP Dr. Sardjito Yogayakarta is classified as moderate (83.3%), whilethe level of performance of the medical records officer at RSUP Dr. Sardjito Yogyakarta is classified as high(50%). Spearman rank correlation test results indicate that there is a relationship with a moderate categorybetween job satisfaction with the performance of medical recorders at RSUP Dr. Sardjito Yogyakarta with asignificance value or p value 0.006 and a correlation coefficient of 0.487.